Breast meat quality of turkey breeder hens at disposal age affected by deep pectoral myopathy - Cavalcanti, Érika Nayara Freire [UNESP] (2021)
Deep pectoral myopathy (DPM) considerably affects the meat quality of commercial poultry, thus representing a challenge to the poultry industry. In this study, we examined the breast meat quality of turkey breeder hens at disposal age affected by different degrees of DPM. Samples were collected from Nicholas turkeys at disposal age (385 d), at an average weight of 12.5 kg, which were reared and slaughtered in the south region of Brazil. The breast was first classified according to the degree of DPM and then samples of the Pectoralis major were collected from birds affected (DPM degrees 2 and 3; n = 20 of each) and nonaffected (normal, absence of lesions; n = 20) by the myopathy. After the affected Pectoralis minor muscle was discarded, the carcasses were released for human consumption by the Federal Inspection Service. The meat affected by the myopathy exhibited color changes (L*, a* and b*) (P < 0.05), especially in the inner surface. Higher (P < 0.05) water-holding capacity, pH, sarcomere length and fat concentration and lower (P < 0.05) shear force and moisture percentage were observed when compared to the normal samples. From this study, can be concluded that the severe condition of deep pectoral myopathy which affects the Pectoralis minor muscle, causes variations in the quality of Pectoralis major muscle of turkey on disposal age. As a raw material, this type of meat has a higher fat content and greater capacity for retaining intracellular water, important attributes to the manufacture of processed products. In this way, the processing is an economically viable alternative to the commercialization of breast meat from birds affected by myopathy.